Asset rotation : the demise of modern portfolio theory and the birth of an investment renaissance - Erickson, Matthew P. (Hoboken, New Jersey : John Wiley & Sons, 2014)
"An all-weather, tactical approach to asset management utilizing Exchange Traded Funds (ETFs)In Asset Rotation, portfolio management pioneer Matthew P. Erickson demonstrates a time-tested approach to asset management that has worked throughout the history of capital markets, in good times and bad. Providing investors with strong participation in rising markets, but more importantly with a discipline to reduce participation in prolonged declines. Over time this revolutionary approach has yielded superior returns, with significantly reduced levels of risk; providing the engine for true, long-term sustainable growth. The investment world as we know it has changed, and the paradigm has shifted. What has worked in the past may no longer work in the future. No longer may bonds be regarded as a safe haven asset class, as for the first time in generations, investors in fixed income face losses as interest rates rise from historical all-time lows. For those adhering to a conventional Modern Portfolio Theory based investment approach to asset management, what was once regarded as safe and stable, may very well soon become our greatest impediment. Asset Rotation provides investors with a practical solution for today's real world problems. This tactical approach to asset management provides us with concrete proof that there is indeed a better way. We are standing on the precipice of an Investment Renaissance. What was previously impossible, is now possible. Find out how. Presents an easy-to-understand price momentum-based approach to investing Illustrates the benefits of asset rotation Offers a systematic approach for securing a sound financial future Provides further insights as to how to customize your own asset rotation portfolio Matthew Erickson gives investors a hands-on resource for how to navigate an increasingly difficult investment landscape, by providing them with keen insights into the most rapidly growing segment of the investment markets"--
"This book will prove that even the lay investor can execute these strategies well enough to amass returns"--
Machine generated contents note: Preface: We stand on the precipice of an Investment Renaissance Acknowledgments Prologue: David & Goliath Chapter 1 Taking the 30,000-Foot View: Where We Are Today The Individual Investor Ockham's Razor Our Current Economic Landscape The Bottom Line Chapter 2 When the Paradigm Shifts: Why What Worked In the Past May No Longer Work In the Future A Primer on Modern Portfolio Theory The Treasury Run Losing Money in Bonds The Bottom Line Chapter 3 Shooting Stars: The Performance Realities of Mutual Fund Ownership The Persistence of Manager Performance The Bottom Line Chapter 4 Beyond the Stars: Suggestions for Investment Selection Criteria The Cost of Investing Identifying Risk Assessing the Investment Environment The Bottom Line Chapter 5 The Landscape Has Changed: The Proliferation of the ETF The ETF: What Is It? A Brief History The Use of ETFs in a Portfolio The Bottom Line Chapter 6 Challenging Convention: An Introduction to Asset Rotation A Time-Tested Approach The 2000s The 1990s The 1980s The 1970s The 1960s The 1950s The 1940s The Great Depression From The Great Depression to Today The Bottom Line Chapter 7 Building a Better Mousetrap: Advanced Asset Rotation Building a Better Mousetrap The 1990s The 2000s From 2010 -- 2012 23 Years: 1999-2012 Going Toe to Toe with the Best The Bottom Line Chapter 8 Choose Your Own Adventure: Building Your Own Asset Rotation Portfolio Choose Your Own Adventure Additional Factors to Consider: Eligible Risk Assets Additional Factors to Consider: Eligible Flight to Safety / Fixed Income Assets Additional Factors to Consider: Criteria for Investment Selection Creating a Scoring System Required Due Diligence The Bottom Line Chapter 9 The Anatomy of Change: Setting Appropriate Expectations Benchmarking Success The Four Seasons When Equity Markets Rise When Equity Markets Fall When Equity Markets Move Sideways When Equity Markets Move Sideways with Volatility The Bottom Line Chapter 10 Letting Go of Your Crutch: Integrating Asset Rotation into Your Overall Approach Letting Go of Your Crutch Asset Rotation as a Core Approach Baby Steps Supplementing Either Equities or Fixed Income Adopting a Core/Satellite Approach The Bottom Line Chapter 11 The Road Ahead: Real World Solutions for a Changing Landscape The Bottom Line About the Author Index.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Portfolio management; Asset allocation; Investment analysis; BUSINESS & ECONOMICS -- Investments & Securities; Asset allocation; Investment analysis; Portfolio management; Electronic books